Redescription of four species of Camelobaetidius Demoulin, 1966 (Ephemeroptera: Baetidae) from Central and North America - Sibaja-Araya, Fabián; Esquivel, Carlos (Zootaxa, 2020)
Four species of Camelobaetidius (C. maidu, C. variabilis, C. kondratieffi, and C. shepardi) are redescribed and diagnosed based on paratype material and original descriptions. Some omissions and inaccurate information in the original descriptions are emended, and illustrations of all taxonomically important structures are provided. Diagnostic characters are improved for a better discrimination from other species across the distribution range of the genus, especially in Central and North America and differences in some important taxonomic characters between these paratypes and the original descriptions are stressed.